Three Decades of Research on Induced Hypocrisy: A Meta-Analysis. (December 2019) - Priolo, Daniel; Pelt, Audrey; Bauzel, Roxane St.; Rubens, Lolita; Voisin, Dimitri; Fointiat, Valerie
Induced hypocrisy is a sequential, two-step, cognitive dissonance procedure that prompts individuals to adopt a proattitudinal behavior. The present meta-analysis of 29 published and nine unpublished induced-hypocrisy studies enabled us to test three key dissonance-related issues. First, is hypocrisy effective in promoting change in behavioral intention and behavior? Our analyses supported the idea that hypocrisy (vs. control) increased both behavioral intention and behavior. Second, does hypocrisy generate psychological discomfort? Results pertaining to this issue were inconclusive due to the small number of studies measuring psychological discomfort. Third, are both steps necessary to generate change? Effect sizes conform to the idea that the transgressions-only condition can increase both behavior and intention. Our meta-analysis raises a number of theoretical issues concerning the psychological processes underlying induced hypocrisy and highlights implications for practitioners.